Ellipsis in complex sentences in the novel “Gone with the Wind” in English and their Vietnamese equivalents in translated version / Đồng Thị Kim Oanh; Supervisor: Assoc.Prof.Dr. Nguyễn Đăng Sửu - Đồng, Thị Kim Oanh
This thesis deals with the ellipsis in complex sentences collected from the novel “Gone with the wind” in English by Margaret Mitchel and their Vietnamese equivalents in translated version by Vu Kim Thu to help the teachers and learners of English master the elliptical phenomena in English complex sentences and use them more accurately and effectively. In the thesis the theoretical background is based on the viewpoints of Randolph Quirk. Et.al (1985). The combination of the descriptive, qualitative, quantitative and comparative methods is used in the thesis. The data was collected from the novel “Gone with the wind” in English by Margaret Mitchel and their Vietnamese equivalents in translated version by Vu Kim Thu. The findings of the study shows that Vietnamese language shares some similarities on the appearance of ellipstical elements as in English complex sentences. It also shows that not all elliptical elements in English complex sentences stay the same in Vietnamese translation version. Some Vietnamese equivalents do not omit elliptical elements as in English version, or they were translated in another ways in accordance with Vietnamese literary style and to persuade the readers. After analyzing the data collected, the research discussed and recommend some implications along with suggestions for further research. It is hoped that this study will be useful for teaching and learning ellipsis in complex sentences. Finally yet importantly, it will help learners of English understand and have appropriate ways to translate English complex sentences bearing ellipsis more persuasively.